Asymmetric atrophy of cervical multifidus muscles in patients with chronic unilateral cervical radiculopathy. Issue 32 (August 2019) - Yun, Yeocheon; Lee, Eun Jeong; Kim, Yong; Kim, Jin Chul; Lee, Seung Ah; Chon, Jinmann
Abstract : Abstract: The purpose of this study was to assess whether the asymmetry of cervical multifidus muscles occurred in radiculopathy patients, and if it did, whether it was related to the chronicity of unilateral cervical radiculopathy by assessing the cross-sectional area (CSA) of multifidus muscles using magnetic resonance imaging (MRI). This study used a retrospective design and was conducted from January 2013 to August 2016. Seventy-seven patients (age 18–65) who had unilateral neck pain, symptom duration of 3 months to 1 year, and who were diagnosed with unilateral 6th cervical radiculopathy by electrodiagnostic testing, were included in study. The CSA of cervical multifidus muscles was measured at the midpoint between the lower margin of the upper vertebra and upper margin of the lower vertebra on axial MRI. Relative CSA (rCSA), which is the ratio of the CSA of muscles to that of the lower margin of C5 vertebra was also obtained. At the C4-5 and C6-7 levels, CSA and rCSA of cervical multifidus muscles showed no statistically difference between the affected and unaffected sides. At the C5-6 level, multifidus muscles were significantly smaller in the affected side (at the C5-6 level, P value of CSA.007 and P value of rCSA.102). The atrophy of multifidus muscles ipsilateral to cervical radiculopathy was observed in patients who had chronic unilateral cervical radiculopathy.